Study and evaluation of nano-structured cellulose fibers as additive for restoration of historical mortars and plasters. (2017) - Rosato, L.; Stefanidou, M.; Milazzo, G.; Fernandez, F.; Livreri, P.; Muratore, N.; Terranova, L.M.
Abstract: UPM bio-fibrils are nano-structured cellulose fibers (nano-fibrils) produced by UPM Kymmene-Corporation, a Finnish company. This paper reports a preliminary study about nano-fibrils to determine their possible use for restoration of historical mortars and plasters. The aim of this study is to investigate the behavior of some mixtures added with nano-fibrils in their properties for conservative purposes. These mixtures reproduce the composition of historical mortars and plasters, made of natural hydraulic lime (NHL 3.5) and river sand. After 28 days of hardening, the properties of specimens with nano-fibrils were compared with untreated one to understand how nano-fibrils interact with inorganic matrix. They influenced the mortar properties in different ways. For example, mechanical tests showed a decrease of flexural and compressive strength as the percentage of nano-fibrils increased. Nevertheless, capillary absorption tests proved that the addition of nano-fibrils was beneficial to the mortar because the final amount of absorbed water was lower for the samples with a higher percentage of nano-fibrils.